1991
DOI: 10.1002/srin.199100451
|View full text |Cite
|
Sign up to set email alerts
|

Rolling and recrystallization textures of bcc steels

Abstract: The rolling and recrystallization texture development of bcc steels is discussed for three examples belonging to three different types of steels, namely deep drawing steels (e.g. low carbon steel), ferritic stainless steels (e.g. Fe16%Cr) and electrical steels (e.g. Fe3%Si).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
123
1
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 244 publications
(133 citation statements)
references
References 5 publications
8
123
1
1
Order By: Relevance
“…The hot rolling and cold rolling textures of ferritic stainless steels are very inhomogeneous through the thickness. [35][36][37] In this study all the textures were measured at the center layer with the strongest fiber texture. 37) Moreover, EBSP measurements were performed using Orientation Imaging MicrographTM (OIM) software equipped in a field emission type Scanning Electron Microscope (accelerated voltage 25 kV, beam step 2 mm).…”
Section: Methodsmentioning
confidence: 99%
“…The hot rolling and cold rolling textures of ferritic stainless steels are very inhomogeneous through the thickness. [35][36][37] In this study all the textures were measured at the center layer with the strongest fiber texture. 37) Moreover, EBSP measurements were performed using Orientation Imaging MicrographTM (OIM) software equipped in a field emission type Scanning Electron Microscope (accelerated voltage 25 kV, beam step 2 mm).…”
Section: Methodsmentioning
confidence: 99%
“…It is found that recrystallization in a cold-worked low carbon steel is mainly controlled by the oriented nucleation theory/grain frequency effect that is governed by the orientational dependence of the stored deformation energy (Hölscher et al, 1991.) The two key recrystallization texture components in steel are {110}<1 1 0> and {554}<22 5 >.…”
Section: Al 1997)mentioning
confidence: 99%
“…11,[25][26][27] In this paper, the {334}͗483͘ and {112}͗110͘ components were calculated to obey an approximate 26°͗110͘ orientation relationship, close to the orientation relationship of coincidence site lattice (CSL)S19a (27°͗110͘) grain boundaries, which display high mobility.…”
Section: Texture Developments During Conventional Processingmentioning
confidence: 99%
“…11,[25][26][27] In this paper, the {334}͗483͘ and {112}͗110͘ components were calculated to obey an approximate 26°͗110͘ orientation relationship, close to the orientation relationship of coincidence site lattice (CSL)S19a (27°͗110͘) grain boundaries, which display high mobility. 28) Therefore, {334}͗483͘ recrystallization texture could have been developed from the scattered cold rolling textures by a 26°͗110͘ selective grain growth in the vicinity of the pre-existed high-mobility CSL-grain boundaries.…”
Section: Texture Developments During Conventional Processingmentioning
confidence: 99%